Authentic Professional Communication in ESP: A Press Release-Based Learning Model - A’thi Fauzani Wisudawati; Jannatul Laily Noviabahari; Moh Farid Mafthuh; Yulius Harry Widodo; Intan Aulia Nastiti (CV Wahana Publikasi, 2025)
The use of authentic materials has become increasingly important in English for Specific Purposes (ESP) instruction, particularly in preparing students for workplace communication contexts. This study investigates the implementation of press releases as authentic materials in teaching English for Business and Professional Communication and examines their impact on students’ communication skills and learning perceptions. The study employed a qualitative case study design involving undergraduate students. The participants were 19 students majoring Business and Professional Communication at a university in Indonesia. Data were collected through classroom observations, students’ writing assignments, and questionnaires. The findings reflect prior studies on authentic materials, which imply that real-world texts improve communicative skills by exposing learners to naturally occurring language and professional practices. It also reveals that press releases were effectively implemented through a genre-based instructional approach consisting of text analysis, collaborative writing, and independent writing activities. The use of authentic press releases contributed positively to students’ professional communication skills, particularly in organizing information, using formal language, developing audience awareness, and understanding workplace discourse conventions. In addition, students demonstrated positive perceptions toward the use of press releases, considering them relevant, engaging, and beneficial for future careers. Although students experienced challenges related to vocabulary and formal writing style, instructional scaffolding and collaborative learning activities helped facilitate comprehension and participation. The study concludes that press releases are valuable authentic materials for ESP classrooms as they bridge classroom learning and real-world professional communication practices.